Analysis of tribotechnical characteristics of self-fluxing coating under rolling and sliding at non-stationary loading - Микосянчик, Оксана Александровна; Ляшенко, Борис Артемович; Агеев, Максим Сергеевич; Лопата, Виталий Николаевич (Technology audit and production reserves, 2016)
This article discusses the possibility of self-fluxing nickel-based alloy for the friction pairs operating under rolling with sliding. The aim of research was to determine the kinetics of changes in the physical and mechanical, anti-wear and anti-friction properties of the sprayed coating of self-fluxing powder PG-AN9 among transmission oil. The method of assessment of tribotechnical properties of the coating is proposed in the start-up mode at step increase in load to the appearance of the first signs of the setting of the contact surfaces. It was established an increase of the normal operation period in sprayed coatings at 5,42 times for the coating thickness increases to 1,2 mm due to effective lubricating effect, low friction coefficient, reducing the specific friction work and reducing the degree of surface coating layers plasticizing by the lubricant components. The results can be used by specialists in the field of repairing and rebuilding worn parts of machines and mechanisms.